Endometrial carcinoma recurrence according to race and ethnicity: An NRG Oncology/Gynecologic Oncology Group 210 Study. Issue 6 (6th November 2017) - Felix, A.S.; Brasky, T.M.; Cohn, D.E.; Mutch, D.G.; Creasman, W.T.; Thaker, P.H.; Walker, J.L.; Moore, R.G.; Lele, S.B.; Guntupalli, S.R.; Downs, L.S.; Nagel, Ci; et al.
Abstract : Non‐Hispanic black (NHB) women are more likely to experience an endometrial carcinoma (EC) recurrence compared to non‐Hispanic white (NHW) women. The extent to which tumor characteristics, socioeconomic status (SES) and treatment contribute to this observation is not well defined. In the NRG Oncology/Gynecology Oncology Group (GOG) 210 Study we evaluated associations between race/ethnicity and EC recurrence according to tumor characteristics with adjustment for potential confounders. Our analysis included 3, 199 NHW, 532 NHB and 232 Hispanic women with EC. Recurrence was documented during follow‐up. We used Cox regression to estimate hazard ratios (HRs) and 95% confidence intervals (CIs) for associations between race/ethnicity and EC recurrence in models stratified by histologic subtype (low‐grade endometrioid, high‐grade endometrioid, serous, mixed cell, carcinosarcoma, clear cell) or stage (I, II, III) and adjusted for age, SES, body mass index, smoking status and treatment. In histologic subtype‐stratified models, higher EC recurrence was noted in NHB women with low‐grade endometrioid (HR = 1.94, 95% CI = 1.21–3.10) or carcinosarcomas (HR = 1.66, 95% CI = 0.99–2.79) compared to NHWs. In stage‐stratified models, higher EC recurrence was noted among NHB women with stage I (HR = 1.48, 95% CI = 1.06–2.05) and Hispanic women with stage III disease (HR = 1.81, 95% CI = 1.11–2.95). Our observations of higher EC recurrence risk among NHB and Hispanic women, as compared to NHW women, were not explained by tumor characteristics, SES, treatment or other confounders. Other factors, such as racial differences in tumor biology or other patient factors, should be explored as contributors to racial disparities in EC recurrence. Abstract : What's new? Cancer of the endometrium (EC), the inner lining of the uterus, shows one of the most prominent racial disparities among common cancers with a 93% higher mortality rate in black as compared with white women. Here, the authors show that race also affects the recurrence rate of EC as non‐Hispanic black and Hispanic women experience a higher cancer recurrence rate within certain subgroups defined by tumor characteristics such as low‐grade endometrioid, carcinosarcoma and stages I and III tumors. The authors note that clinicians treating women with EC should be aware of racial differences in recurrence risk, particularly among women diagnosed with these specific tumor characteristics.